2010
DOI: 10.1055/s-0029-1243200
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Tumor of the Frontal Bone in an 18-Month-Old Girl: A Case Report

Abstract: Although rare, GCTs should be taken into consideration as a differential diagnosis of rapidly enlarging cranial mass lesions in pediatric patients. Gross total surgical excision eliminates the potential risks of adjuvant radiotherapy. However, considering the aggressive nature and potential malignancy of these lesions, careful long-term clinical and imaging follow-up is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It is unclear as to whether the radiotherapy was ultimately necessary. Two cases involving the cranial vault, documented by Coumbaras et al [15] and Ulu et al [16], employed no post-operative radiotherapy and no recurrence was observed during the follow-up period.…”
Section: Discussionmentioning
confidence: 93%
“…It is unclear as to whether the radiotherapy was ultimately necessary. Two cases involving the cranial vault, documented by Coumbaras et al [15] and Ulu et al [16], employed no post-operative radiotherapy and no recurrence was observed during the follow-up period.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, Kamoshima et al described a 2-year-old female patient with recurrent GCT of the frontal bone that underwent two partial surgical removals of the tumor with recurrence before total resection of the lesion, surrounding bone, and frontal base dura mater was curative [14]. The reported incidence in the literature of non-recurrence after total resection of a frontal bone lesion has been up to 30 months [15]. If total resection cannot be achieved, the combination of subtotal resection and radiation therapy shows a similar low recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…4 In the English literature, only three cases reported of such tumor involving the frontal bone in adults and one pediatric patient. [5][6][7] Only one of these cases was filling the frontal sinus. Hlavácek et al described their first 2 cases report of frontal giant cell tumor as a polyostotic form of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…There are only 3 cases reported in the English literature as a GCT of frontal bone in adult patients and 1 pediatric patient. [5][6][7] Only one of them was a frontal sinus occupying mass. 5 None of these case reports included a complete clinical, radiological and histopathological demonstration.…”
Section: Introductionmentioning
confidence: 99%